IMPLEMENTATION OF COOPERATIVE LEARNING MODELS OF JIGSAW TYPE IN ECONOMIC LESSONS TO INCREASE STUDENT ACTIVITY AND LEARNING OUTCOMES - Citra, Nyoman Yuliana (Journal of Psychology and Instructions, 2018)
This study is aimed to increase the activeness and the learning achievement through the implementation of cooperative learning model by using jigsaw on the Economy subject of the tenth grade students at IPS 1 class of SMA Negeri Bali Mandara academic year 2017/2018. The data was collected by using observation method and written test. Afterwards, the data was analyzed by using the quantitative descriptive analysis. The result of this study showed that:Â  (1) the implementation of cooperative learning model by using jigsaw on the Economy subject had increased the students learning activeness of the tenth grade students at IPS 1 class of SMA Negeri Bali Mandara academic year 2017/2018. This result was proven by the average score of the students learning activeness from the cycle I was 3,02 which belongs to active category and the score on the cycle II was 3,59 which is also in the category of active. (2) The implementation of cooperative learning model by using jigsaw on the Economy subject has increased the students learning achievement of the tenth grade students at IPS 1 class of SMA Negeri Bali Mandara academic year 2017/2018. The result showed that the students learning completeness on the cycle I was 43,48% with the class average score was 76,88 and the students learning completeness on the cycle II had increased up to 100,00%Â  with the class average score was 86,31.